Analisis Perbandingan Mazhab tentang Pelaksanaan Mediasi dengan Media Telekonferensi - Dewi, Nurul Aulia; Talli, Abdul Halim (Universitas Islam Negeri Alauddin Makassar, 2020)
This article seeks to present a comparison of mediation with teleconference media, both within the PERMA and the scholars of the sect. Mediation is an attempt to resolve conflicts by engaging neutral mediators who do not have the authority to make decisions that help the parties in dispute to reach a resolution or solution accepted by both parties. The multidisciplinary approach used in this article is a juridical, sociological, theological-normative and managerial approach. This article is library research, a study by writing, clarifying, and making data obtained from various written sources. The method of data collection is to use document techniques (library studies). Quoting and analyzing data with document techniques is intended to collect related data contained in documents in the form of books, journals, and research results in the form of thesis, thesis, and dissertation. The results found that the most notable differences regarding the limits of mediation with teleconference media were found in the dissent of the Sect scholars. The Shafi and Hanbali sects argue that the ideal age in marriage is 15 years, while Abu Hanfah argues that the age of maturity comes at 19 years of age for women and 17 years for men, as is the case with Imam Malik arguing that the ideal age of manhood is 18 years for both men and women. The differences between the Imams of the Sect are influenced by the environment and culture in which they live. However, in Islamic law itself there is never a very firm limit, but the most basic thing about the age limit of marriage is that it is already in place